PERANAN METODE PENYIMPANAN BAHAN MAKANAN DALAM MENINGKATKAN KUALITAS MAKANAN DI HOTEL BINTANG LABUHAN BAJO FLORES - Zakharia, Friend; Adiputra, Fahri; Meko, Pasifikus (Jurnal Ilmiah Global Education, 2023)
Bintang Flores Hotel is a 4 -star hotel in Labuan Bajo Flores It has types of food ranging from appetizers to desserts that are served at breakfast until dinner so that the quality of the food served is good, a method of storing food ingredients is needed so that the quality of the food served every day can be guaranteed. This research is descriptive descriptive qualitative. The data is done by collecting primary data and secondary data. The data and information obtained through field research were then analyzed. Data reduction techniques, data presentation, and triangulation were used in analyzing the data. The results showed that the storage method has a role in food quality. Storage can be done in various ways, starting from food labeling, maintaining the circulation of goods using the FIFO system, and checking both the temperature and the expiration time of the goods. These various methods can improve the quality of food from various sides ranging from attractive appearance, appropriate taste, and attractive color to good texture so that it can make consumers interested in enjoying the food